2014
DOI: 10.1007/s00404-014-3411-5
|View full text |Cite
|
Sign up to set email alerts
|

Pain control and quality of life after laparoscopic en-block resection of deep infiltrating endometriosis (DIE) vs. incomplete surgical treatment with or without GnRHa administration after surgery

Abstract: GnRHa administration is followed by a temporary improvement of pain in patients with incomplete surgical treatment. It seems that it has no role on post-surgical pain when the surgeon is able to completely excise DIE implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 25 publications
4
47
0
4
Order By: Relevance
“…Our results showed that postoperative QOL was improved in both groups, which was also in agreement with the previous study [29,[32][33][34][35]. The QOL in incomplete surgery is comparable with the QOL in the complete surgery group in the physical, social, environmental and selfassessment aspect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that postoperative QOL was improved in both groups, which was also in agreement with the previous study [29,[32][33][34][35]. The QOL in incomplete surgery is comparable with the QOL in the complete surgery group in the physical, social, environmental and selfassessment aspect.…”
Section: Discussionsupporting
confidence: 92%
“…There was a greater improvement in psychological score in complete excision group than in in-complete excision group, which implicated that the reassurance of complete excision also had a psychological effect on the patients. In Angioni's study [35], at 1-year followup patients treated with complete resection showed significant improvement in physical function, general health, and vitality in comparison to 12 months follow-up of the patients who underwent an incomplete surgical treatment. This difference might due to that our patients were given GnRH agonist followed by contraceptive pills or merely contraceptive pills after surgery.…”
Section: Discussionmentioning
confidence: 93%
“…This operation has been conducted by operative laparoscopy as described elsewhere [41,42]. Moreover, clinicians use laparoscopic surgical resection in cases of deep endometriosis infiltrating the uterosacral ligaments [43][44][45][46][47]. In this case, it is necessary to conduct ureterolysis to be able to execute the uterosacral ligament (USL) nodule completely without any risk of ureter injury.…”
Section: Choosing the Best Surgical Approachmentioning
confidence: 99%
“…Cette diminution était plus marquée au cours de premiers six mois, ensuite les valeurs des volumes restaient sensiblement stables [8], probablement en rapport avec la nature histologique des nodules d'endométriose profonde qui sont composés dans une proportion d'environ 75 % du tissu fibro-conjonctif et de cellules musculaires lisses indifférentes à l'action du traitement hormonal [12]. Dans une autre étude comparant l'évolution postopératoire des douleurs chez les patientes ayant bénéficié d'une chirurgie de l'endométriose profonde, les scores des douleurs enregistrés après une résection complète étaient comparables avec ceux observés après une résection incomplète associée à un traitement continu par des analogues de la GnRH [13].…”
Section: « Le Traitement Médical Ne Prévient Pas La Maladie Mais Seulunclassified
“…La survenue des ces événements justifie dans notre opinion plutôt le remplacement du médicament incriminé par un autre de composition différente que l'arrêt complet du traitement médical, qui est généralement suivi par la reprise des douleurs au cours des six mois suivants [13].…”
Section: « Le Traitement Médical Prolongé Entraîne Des Effets Secondaunclassified